Studying the effect of the magnetic field on the growth of the two fungi (Eurasian Journal of Research, Development and Innovation, 2024)
The current study aimed to determine the effect of the magnetic field of the positive and negative poles on the growth and vitality of the fungal isolate of the two fungi Trichoderma sp and Alternaria sp, as it showed the following: There was a direct increase in the diameter of the resulting colonies for both fungal genus Trichoderma sp and Alternaria sp. The highest increase in the diameter of the colonies was under the influence of intensity. 200mT, and the time factor had a boosting effect on the growth of the fungi Trichoderma sp and Alternaria sp, represented by stimulating growth when exposed to the magnetic field for seven days, as the magnetic field with its different intensities used in the research and exposure durations had no significant effect on the water exposed to it